Phosphate Regulates Osteopontin Gene Transcription - Fatherazi, S. (SAGE Publications, 2009)
Extracellular inorganic phosphate (ePi) is a key regulator of cementoblast behavior, both in vivo and in vitro, and results in a marked increase in osteopontin expression in vitro. To examine the molecular mechanisms involved in ePi induction of osteopontin gene expression, we transfected a series of osteopontin promoter-luciferase constructs into OCCM-30 cementoblasts. Our results demonstrate that ePi can directly induce osteopontin gene transcription. The region responsive to ePi signaling was localized to a 53-bp region of the promoter between -1454 and -1401 that contains a glucocorticoid response element (GRE). Mutation of the GRE abolished the ePi response, suggesting that glucocorticoid receptor (GR) signaling is required for ePi-mediated transcription. In addition, treatment of cells with the GR antagonist RU-486 (Mifepristone) prevented promoter activation by ePi. The results presented support a model demonstrating that inorganic phosphate regulates OPN gene transcription in cementoblasts through a pathway that requires a functional GR. Abbreviations: BSP, bone sialoprotein; DMP1, dentin matrix protein 1; EMSA, Electrophoretic mobility shift assay; ePi, extracellular inorganic phosphate; GRE, glucocorticoid response element; GR, glucocorticoid receptor; OPN, osteopontin; Pi, inorganic phosphate; Q-PCR, quantitative PCR.